Back to the Future: The Past, Present and Future of Resource Development in a Changing Arctic - Hacquebord, Louwrens (Journal of Northern Studies, 2010)
In 2007 a Russian flag was placed on the seafloor at the North Pole to mark the Russian United Nation Convention on the Law of the Sea (UNCLOS) territorial claim on the slope of the continental shelf in the Arctic Ocean. This activity drew the attention of the world to the North Pole region and the resources expected to be found there. It also made clear that a new race for the natural resources in the North Pole region was at the point of beginning. This article will discuss the relation between climate change, resource development and geopolitics. It will place recent political events in a historical context and will finish by considering some future political developments.